Efficacy and safety of RET-TKI in advanced RET-rearranged non-small cell lung cancer in China: a real-world retrospective chart review - Siyu Lei; Linyan Tian; Lu Yang; Yaning Yang; Junling Li; Xingsheng Hu; Xuezhi Hao; Haiyan Xu; Yan Wang (BMC Cancer)
Abstract Background Selective RET inhibitors have been approved by the Chinese government for the treatment of RET-rearranged non-small cell lung cancer. This study aimed to illustrate the efficacy and safety of selective RET inhibitors in a real-world clinical context in China. Methods Patients with locally advanced or metastatic non-small cell lung cancer (NSCLC) harboring RET rearrangement and receiving RET tyrosine kinase inhibitors (RET-TKI) in the real world were enrolled in this retrospective study. Clinical data, including baseline clinicopathological information, efficacy parameters such as objective response rate (ORR) and progression-free survival (PFS), and adverse events (AEs), were collected from the electronic medical record system. The pattern of treatment failure of first-line RET-TKI was also described. Results Fifty-one patients were enrolled in this study. RET-TKI induced an ORR of 73.1% and a median PFS (mPFS) of 22.7 months (95%CI, 11.7–33.7) in the first-line setting. The ORR and mPFS were 58.3% and 17.7 months (95%CI, 9.1–26.2), 55.6% and 14.7 months (95%CI, 12.6–16.8) in the second-line and later-line settings, respectively. No significant difference was observed among different application lines with respect to the ORR (P = 0.534) or PFS (P = 0.795). In the first-line setting, RET-TKI significantly prolonged PFS compared to other regimens including chemotherapy-based regimens, multikinase inhibitors and other systemic regimens without chemotherapy (P < 0.05). Poor ECOG performance status was related to shorter PFS (P = 0.018). The most common AEs of grade 3 or worse were a decreased neutrophil count (11.4%) and anemia (11.4%). No new AEs or grade 5 AEs were observed. Brain metastasis was one of the most common patterns of treatment failure. In patients with baseline brain metastasis, the intracranial ORR was 50%, and the DCR was 100%. Conclusions RET-TKI had favorable efficacy and safety in real-world contexts in China and should be considered the preferred choice for first-line treatment in RET-rearranged NSCLC patients.